Community Awareness towards Inclusive Education for Children with Learning Disabilities in Myanmar Educational Context - Lum Pan; Thea Czaireena T. Dizon (ETDC: Indonesian Journal of Research and Educational Review, 2026)
Although Myanmar has adopted an international legal framework through the Education Law (2007) and the Child Rights Law (2019), significant gaps exist between formal policies and practical implementation. Public awareness is still hampered by negative stigma, infrastructure constraints, and the influence of certain cultural and religious beliefs that contribute to the exclusion of children with learning disabilities. This literature review aims to explore the level of public awareness of inclusive education for children with learning disabilities in Myanmar and identify factors that hinder the transition from policy to practical inclusion. This study used a literature review method by analyzing various policy documents, previous studies, and reports on the educational context in Myanmar, including its impact on ethnic minority groups and children with disabilities. Findings indicate that the main challenges to inclusion in Myanmar include sociocultural factors such as the concept of "karma" that reinforces stigma, as well as a lack of school preparedness. Although school stakeholders generally support inclusion, they are hampered by a lack of specialized training, a rigid curriculum, overcrowded classes, language barriers, and uncertainty resulting from the ongoing political conflict. This leads many families to still choose special schools (separate) over inclusive schools. This article provides strategic recommendations for policymakers and education practitioners in Myanmar to focus not only on legal aspects but also on investing in teacher training, providing adequate infrastructure, and community engagement campaigns. The study emphasizes the importance of viewing disability as part of human diversity to create an equitable education ecosystem for all children.